2016
DOI: 10.1373/jalm.2016.021006
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Biomarkers and Risk of Cardiovascular Disease: A Laboratory Medicine Best Practices (LMBP) Systematic Review

Abstract: Background Controversy exists about the incremental utility of nontraditional lipid biomarkers [e.g., apolipoprotein (apo) B, apo A-I, and non-HDL-C] in improving cardiovascular disease (CVD) risk prediction when added to a conventional model of traditional risk factors (e.g., total cholesterol, LDL cholesterol, HDL cholesterol, sex, age, smoking status, and blood pressure). Here we present a systematic review that was conducted to assess the use of nontraditional lipid biomarkers including apo B, apo A-I, apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 60 publications
3
31
0
1
Order By: Relevance
“…Our results are in accord with those of a previous study that did not detect a relationship between non-HDL and cardiovascular disease outcomes in a cohort of patients with prevalent coronary artery disease [42]. However, a recent systematic review of studies, including patients with multiple risk factors for cardiovascular disease, found no evidence that non-HDL markers predict the occurrence of cardiovascular events [43]. Therefore, there is a need for more research in this field.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in accord with those of a previous study that did not detect a relationship between non-HDL and cardiovascular disease outcomes in a cohort of patients with prevalent coronary artery disease [42]. However, a recent systematic review of studies, including patients with multiple risk factors for cardiovascular disease, found no evidence that non-HDL markers predict the occurrence of cardiovascular events [43]. Therefore, there is a need for more research in this field.…”
Section: Discussionsupporting
confidence: 90%
“…Наиболее крупные исследования AMORIS и INTER-HEART показали важную роль АпоВ в развитии не только неблагоприятных сердечно-сосудистых исходов, но и атеросклероза [32][33][34][35]. Эти данные подтверждаются и рядом исследований, завершившихся О р и г и н а л ь н ы е и с с л е д о в а н и я в последние годы [10,26,[36][37][38]. В нашей работе при анализе неблагоприятных исходов ХНИЗ также было показано, что их наилучшим предиктором был АпоВ > 180 мг/дл.…”
Section: Discussionunclassified
“…Other biomarkers include lipoproteins and C-reactive protein, and have evidence that they are not effective to be added to risk assessment tools. In conclusion, no solid evidence is available now to promote using biomarkers during the management of CVD [6] .…”
Section: Biomarkersmentioning
confidence: 98%